2020
DOI: 10.1111/ffe.13328
|View full text |Cite
|
Sign up to set email alerts
|

Research on the fatigue properties of sub‐heat‐affected zones in X80 pipe

Abstract: Pipeline transmission is an essential means of oil and gas transportation, but its safety is threatened by fatigue fracture that generally occurs in the heat-affected zone (HAZ) adjacent to welded joints of the pipeline. Therefore, it is important to determine the fatigue properties of HAZ. In this work, the microstructure and mechanical properties in the HAZ of a X80 pipe were accurately simulated by thermal simulation. The fatigue life and crack growth rate of typical sub-HAZ were tested. The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Crack propagation tests on different heat affected zones, that is, coarse grained, fine grained, which resembled single pass welds and reheated coarse grained heat affected zones resembling multi-pass welds along with the base metal itself were carried out in Kim et al 1 and results showed that the crack growth rate was fastest in the reheated coarse grained HAZ, whereas the base metal showed the best fatigue crack resistance. Also, the crack propagation rate in fine grained HAZ was slower than in the coarse grained HAZ, which was also found in Qiu et al 2 and Tsay et al 3 In Xu et al 4 it was found that the fine grained HAZ had a lower fatigue life than the course grained HAZ.…”
supporting
confidence: 58%
“…Crack propagation tests on different heat affected zones, that is, coarse grained, fine grained, which resembled single pass welds and reheated coarse grained heat affected zones resembling multi-pass welds along with the base metal itself were carried out in Kim et al 1 and results showed that the crack growth rate was fastest in the reheated coarse grained HAZ, whereas the base metal showed the best fatigue crack resistance. Also, the crack propagation rate in fine grained HAZ was slower than in the coarse grained HAZ, which was also found in Qiu et al 2 and Tsay et al 3 In Xu et al 4 it was found that the fine grained HAZ had a lower fatigue life than the course grained HAZ.…”
supporting
confidence: 58%
“…The heat input of the thermal cycles was 45 kJ cm -1 , mimicking the practical production condition. The peak temperatures at different distances from the weld metal were calculated according to the previous studies [16]. The welding heat cycle processes and the heating and cooling parameters are provided in Figure 2 and Table 2.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
“…However, as is well‐known, the fatigue strength of a welded component in presence of multiaxial cyclic loading is significantly lower than that of an unwelded one (even if the components are made of the same material) 2 . In particular, the factors causing the above strength reduction 3–5 are residual stresses, 6–9 thermal distortions, 10 defects caused by partial penetration, 11 and material microstructural imperfections 12 …”
Section: Introductionmentioning
confidence: 99%
“…2 In particular, the factors causing the above strength reduction [3][4][5] are residual stresses, [6][7][8][9] thermal distortions, 10 defects caused by partial penetration, 11 and material microstructural imperfections. 12 Moreover, complex time variable load histories applied to welded components result in severe stress/ strain gradients at the weld toes/roots leading to fatigue damage near such critical regions.…”
Section: Introductionmentioning
confidence: 99%